Interlimb Transfer of Grasp Orientation is Asymmetrical - Victor Frak; D. Bourbonnais; I. Croteau; H. Cohen (The Scientific World Journal)
One the most fundamental aspects of the human motor system is the hemispheric asymmetry seen in behavioral specialization. Hemispheric dominance can be inferred by a contralateral hand preference in grasping. Few studies have considered grasp orientation in the context of manual lateralization and none has looked at grasp orientation with natural prehension. Thirty right-handed adults performed precision grasps of a cylinder using the thumb and index fingers, and the opposition axis (OA) was defined as the line connecting these two contact points on the cylinder. Subjects made ten consecutive grasps with one hand (primary hand movements) followed by ten grasps with the other hand (trailing movements). Differences between primary and trailing grasps revealed that each hemisphere is capable of programming the orientation of the OA and that primary movements with the right hand significantly influenced OA orientation of the trailing left hand. These results extend the hemispheric dominance of the left hemisphere to the final positions of fingers during prehension.